Kriteria Karya Penggemar Fanfiction Sebagai Karya Turunan Yang Sah Dalam Undang-Undang Hak Cipta Indonesia (RechtJiva, 2025)
Fanfiction was one of the works that fans created in the result of fan labour which requires the original works of fiction to create a new story by adding or transforming the element from the previous work. Fanfiction was considered to be a work in legal grey area but with the thorough analysis case per case, the fanfiction could be protected as long as it fulfilled the copyright ability. This research is a normative juridical study that examines the legal issues based on the criteria for fanfiction as derivative works protected under Law Number 28 of 2014 and compares it with the United States Copyright Act of 1976. It also analyse the appropriate regulation regarding copyright limitations in Article 44 paragraph (1) letter a of Law Number 28 of 2014. The findings indicate that fanfiction can be protected as derivative works under Law Number 28 of 2014 if it meets the copyrightability standards, namely originality, creativity, and fixation. Furthermore, legally valid fanfiction should be non-commercial in nature, draw elements or substance from the public domain, be categorized as parody or criticism, and its use must be in accordance with Articles 43, 44, and 46 of Law Number 28 of 2014, while respecting the reasonable interests of the original creator or copyright holder. The appropriate legal framework for assessing the reasonable interest of fanfiction that does not harm the creator should consider the purpose, nature, amount and substantiality of the portion used, and the potential market impact on the original work.